1999
DOI: 10.1083/jcb.147.2.235
|View full text |Cite
|
Sign up to set email alerts
|

The Karyopherin Kap122p/Pdr6p Imports Both Subunits of the Transcription Factor Iia into the Nucleus

Abstract: We discovered a nuclear import pathway mediated by the product of the previously identified Saccharomyces cerevisiae gene PDR6 (pleiotropic drug resistance). This gene product functions as a karyopherin (Kap) for nuclear import. Consistent with previously proposed nomenclature, we have renamed this gene KAP122. Kap122p was localized both to the cytoplasm and the nucleus. As a prominent import substrate of Kap122p, we identified the complex of the large and small subunit (Toa1p and Toa2p, respectively) of the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 53 publications
2
54
0
Order By: Relevance
“…How each Kap recognizes specific cargo proteins has been the subject of intense study. The only characterized cargo proteins of Kap122 are two TFIIA subunits, Toa1 and Toa2 (63). In this study, we have identified four potential cargo proteins of Kap122: Wtm1, Wtm2, ␤, and ␤Ј.…”
Section: Discussionmentioning
confidence: 95%
“…How each Kap recognizes specific cargo proteins has been the subject of intense study. The only characterized cargo proteins of Kap122 are two TFIIA subunits, Toa1 and Toa2 (63). In this study, we have identified four potential cargo proteins of Kap122: Wtm1, Wtm2, ␤, and ␤Ј.…”
Section: Discussionmentioning
confidence: 95%
“…Hence, despite their functional divergence these two histone-fold heterodimers rely on the same import mechanism to translocate through the NPC. Interestingly, for importin 13 the most similar protein from S. cerevisiae is Pdr6p/karyopherin 122, which translocates the NC2 antagonist transcription factor IIA into the nucleus (68). The identity of Pdr6p with importin 13 is too low to regard it as a clear orthologue (40).…”
Section: Nc2␣ (mentioning
confidence: 99%
“…The localization of GR-GFP was monitored in 14 yeast strains each deficient in a different nuclear transport receptor: CRMI (Stade et al, 1997), CSEI (Xiao et al, 1993), Kap95 (Iovine et al, 1995), Kap104 (Aitchison et al, 1996), Kap123 (Seedorf and Silver, 1997), LOS1 (Hopper et al, 1980), MSN5 (Kaffman et al, 1998a), MTR10 (Kadowaki et al, 1994), NMD5 (He and Jacobson, 1995), PSEI (Seedorf and Silver, 1997), SRP1 (Yano et al, 1992), SXM1 (Seedorf and Silver, 1997), Kap114 (Morehouse et al, 1999;Pemberton et al, 1999), and PDR6 (Titov and Blobel, 1999). Yeast strains PSY580, pse1-1, PSY1200, and PSY902 have been described (Seedorf and Silver, 1997).…”
Section: Yeast Strains Handling Transformations and Localization Smentioning
confidence: 99%